2006
DOI: 10.1124/mol.106.026955
|View full text |Cite
|
Sign up to set email alerts
|

The Important Role of Bcrp (Abcg2) in the Biliary Excretion of Sulfate and Glucuronide Metabolites of Acetaminophen, 4-Methylumbelliferone, and Harmol in Mice

Abstract: The role of Mrp2, Bcrp, and P-glycoprotein in the biliary excretion of acetaminophen sulfate (AS) and glucuronide (AG), 4-methylumbelliferyl sulfate (4MUS) and glucuronide (4MUG), and harmol sulfate (HS) and glucuronide (HG) was studied in Abcc2(Ϫ/Ϫ), Abcg2(Ϫ/Ϫ), and Abcb1a(Ϫ/Ϫ)/Abcb1b(Ϫ/Ϫ) mouse livers perfused with the respective parent compounds using a cassette dosing approach. Biliary clearance of the sulfate conjugates was significantly decreased in Bcrp-deficient mouse livers, resulting in negligible bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 23 publications
6
68
0
1
Order By: Relevance
“…Because Bcrp is directly involved in transporting 4MUG into bile, using eq. 4.1 and the excretory clearance values (Cl Bile WT ϭ 88 l/min/g liver and Cl Bile KO ϭ 24 l/min/g liver) reported by Zamek-Gliszczynski et al (2006c), f e, Bile of Bcrp is calculated to be 0.73. Equation 3 predicts the decrease in biliary recovery of 4MUG to be 3.7-fold; experimentally a 2.1-fold decrease was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Because Bcrp is directly involved in transporting 4MUG into bile, using eq. 4.1 and the excretory clearance values (Cl Bile WT ϭ 88 l/min/g liver and Cl Bile KO ϭ 24 l/min/g liver) reported by Zamek-Gliszczynski et al (2006c), f e, Bile of Bcrp is calculated to be 0.73. Equation 3 predicts the decrease in biliary recovery of 4MUG to be 3.7-fold; experimentally a 2.1-fold decrease was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, BCRP accepts a variety of sulfate conjugates of xenobiotics as substrates, leading to the hypothesis that Bcrp is involved in the efflux of sulfate conjugates formed intracellularly by SULT. Indeed, it has been demonstrated that Bcrp is involved in the efflux of sulfate conjugates in the kidney (Mizuno et al, 2004), liver (Zamek-Gliszczynski et al, 2006;Enokizono et al, 2007), and jejunum (Adachi et al, 2005).…”
mentioning
confidence: 99%
“…ABCG2 also transports glucuronide and sulfate conjugates (Mizuno et al, 2004;Zamek-Gliszczynski et al, 2006). ABCG2/BCRP expression is high in rat kidney and intestine .…”
mentioning
confidence: 99%